Peran AMDAL Dalam Mengawal Etika Bisnis Terhadap Lingkungan Dalam Perspektif Ekonomi Syariah - Devid Frastiawan Amir Sup (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
Environment is a very important thing to maintain and preserve. From the perspective of religion or ethics there is has been done. But in the development of human life, it seems that the impact of industrialization begin to cause various enviromental problems. Therefore, regulation that relating to the production in a business and/or activity are needed, one of which is EIA-Environmental Impact Assessment (in Indonesia usually called by Amdal). This study aims to describe the role of EIA for guarding bussiness ethics on the environtment. The method is use qualitative-decriptive-literature. Result from this study is the existence of “Kerangka Acuan,” “Andal,” and “RKL-RPL” in EIA documents can be an instrument for guarding this ethics, in other side there are contain a “mashlahah” to maintain and preserve the environment. Keywords: Environtment, EIA, Ethics